Improving estimates of the illicit cigarette trade through collaboration: lessons from two studies of Malaysia - Kunji Koya, Ridzuan; Robert Branston, J.; Gallagher, Allen W.A.; Bui, Wency Kher Thinng; Ross, Hana; Mohamed Nor, Norashidah (BMJ, 2024)
This paper critically analyses contrasting estimates of Malaysia’s illicit cigarette trade in 2011, 2015 and 2019 by Bui et al and Koya et al who previously produced independent estimates at about the same time using tax gap analysis. Collaboration between the two authors’ teams emerged due to the discrepancies in their results, generating this paper to explore the methodological issues identified and hence produce revised estimates of the rate of illicit. Key issues identified were: Bui et al’s assessment of legally imported cigarettes impacting all years; their exclusion of ad valorem duty affecting the 2011 and 2015 estimates; Koya et al overlooked the value of cigarettes for export market in their ad valorem calculation and used the sales value of imported tobacco/tobacco products, not just cigarettes, both of which impact estimates for 2011 and 2015. Recalculations using Koya et al’s consumption data reveal that in 2019, illicit cigarettes accounted for about 70% of the market, which is higher than Bui et al’s estimate (38%) but slightly lower than Koya et al’s (72%). For 2011 and 2015 where ad valorem applied, the corrected estimates show a share of the illicit cigarette market of approximately 41.1% and 52.7%, respectively, differing from Bui et al’s 0% in 2011 and 29.6% in 2015, and Koya et al’s 51% in 2011 and 55% in 2015. This paper provides essential lessons for addressing methodological issues between authors’ teams and updated estimates of Malaysia’s illicit cigarette trade, verifying that Malaysia faces a substantial illicit cigarette trade problem.